1983
DOI: 10.1071/ph830473
|View full text |Cite
|
Sign up to set email alerts
|

Cross Sections for Electron?Carbon Monoxide Collisions in the Range 1?4 eV

Abstract: The scattering of electrons from CO molecules has been studied over the energy range from 1 to 4 eV by analysing drift velocity data for pure CO and CO-inert gas mixtures at 294 K. The validity of using the so-called 'two term approximation' for the velocity distribution function in the solution of the Boltzmann equation to analyse drift velocity data for the pure gas (and thus also for the gas mixtures) has been established. The momentum transfer cross section for CO has been determined in the energy range 1-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
0

Year Published

1987
1987
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 4 publications
3
35
0
Order By: Relevance
“…Under certain conditions, Haddad and Milloy (1983) reported large background currents due to negative ions in their drift velocity experiments which prevented them from making measurements at pressures greater than 1 kPa and E/N less than 10 Td. Mass spectrometric analysis of the gas from the cylinder of CO (Matheson Research Grade) used by them revealed that low levels of impurity were present which apparently did not affect their values of Vdr (except perhaps at E/N = 10 Td-see Section 4) but were the major source of the background.…”
Section: (B) Measurements Of the Diffusion Coefficient To Mobility Ratiomentioning
confidence: 99%
See 2 more Smart Citations
“…Under certain conditions, Haddad and Milloy (1983) reported large background currents due to negative ions in their drift velocity experiments which prevented them from making measurements at pressures greater than 1 kPa and E/N less than 10 Td. Mass spectrometric analysis of the gas from the cylinder of CO (Matheson Research Grade) used by them revealed that low levels of impurity were present which apparently did not affect their values of Vdr (except perhaps at E/N = 10 Td-see Section 4) but were the major source of the background.…”
Section: (B) Measurements Of the Diffusion Coefficient To Mobility Ratiomentioning
confidence: 99%
“…Drill with values calculated using the Haddad and Milloy (1983) cross sections shows that some modifications to their cross sections are required. This is to be expected given the discrepancies between the calculated and measured values of DTIIl shown in Fig.…”
Section: Vibrational Excitation Cross Sections a Comparison Of Our Nmentioning
confidence: 99%
See 1 more Smart Citation
“…Different scattering models can be constructed by choosing different types of expansions for the target wave function (Φ N i ) and the corresponding L 2 configurations in equation (1). Generally three different models are used, namely, the static exchange (SE), SE plus polarization (SEP) and the close-coupling (CC) models.…”
Section: Theorymentioning
confidence: 99%
“…This resonance has been wellcharacterised experimentally [1][2][3][4][5] and is the subject of a number of theoretical studies [3,[6][7][8][9]. This resonance provides the main mechanism for electron impact vibrational excitation [9,10] but lies too low in energy to lead to dissociative electron attachment (DEA) unless the CO target is also vibrationally excited [10].…”
Section: Introductionmentioning
confidence: 99%